2016
DOI: 10.23910/ijbsm/2016.7.2.1494a
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Water and Nutrient Requirement through Drip Fertigation in Aerobic Rice

Abstract: A field experiment was conducted during Kharif 2012 at Zonal Agricultural Research Station, Bengaluruin red sandy loam soil (pH-6.9; OC-0.6%) with medium available nitrogen (348 kg ha-1), phosphorous (36.13 kg ha-1) and potassium (244 kg ha-1) to optimize water and nutrient requirement of aerobic rice (Oryza sativa L.) through drip fertigation. The experiment was laid out in Randomized Complete Block Design (RCBD) with 15 treatments. The variety used was MAS 946-1. Drip fertigation significantly influenced the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 0 publications
0
0
0
Order By: Relevance
“…Dry matter production increased with increased level of water and nutrients (T 9 ) due to water soluble fertilizer through fertigation resulted in continues supply of nutrients besides maintaining optimum water availability which lead to higher uptake of nutrients which in turn good soil aeration throughout crop growth period might have favored faster cell division and elongation focused ultimately increased plant height, tiller numbers, more number of leaves and leaf area development leading to maintain total dry matter accumulation. Similar evidence was confined with findings of Kombali et al (2016), Yamuna et al (2018) and Mariyappillai et al (2022). And these may be attributed to the production of higher number of tillers and leaves because of higher uptake of moisture and nutrients due to maintenance frequent application of irrigation and use of water-soluble fertilizers.…”
Section: Growth Parameterssupporting
confidence: 86%
See 1 more Smart Citation
“…Dry matter production increased with increased level of water and nutrients (T 9 ) due to water soluble fertilizer through fertigation resulted in continues supply of nutrients besides maintaining optimum water availability which lead to higher uptake of nutrients which in turn good soil aeration throughout crop growth period might have favored faster cell division and elongation focused ultimately increased plant height, tiller numbers, more number of leaves and leaf area development leading to maintain total dry matter accumulation. Similar evidence was confined with findings of Kombali et al (2016), Yamuna et al (2018) and Mariyappillai et al (2022). And these may be attributed to the production of higher number of tillers and leaves because of higher uptake of moisture and nutrients due to maintenance frequent application of irrigation and use of water-soluble fertilizers.…”
Section: Growth Parameterssupporting
confidence: 86%
“…This might be owing to less nutrient uptake results in reduced soil moisture levels at root zone depth, which prevents assimilates from being transferred to the grains. Similar findings were too accounted by Kombali et al (2016). There was no significance difference in harvest index among the treatments during both the year of experimentation.…”
Section: Yieldsupporting
confidence: 66%
“…This might be owing to less nutrient uptake results in reduced soil moisture levels at root zone depth, which prevents assimilates from being transferred to the grains. Similar findings were too accounted by Kombali et al (2016).…”
Section: Grain Yieldsupporting
confidence: 53%
“…Water productivity with respect to irrigation was influenced by the irrigation schedules in drip irrigation and the highest water productivity was obtained with irrigation scheduling at 100 percent Epan (Rao et al, 2016). Kombali et al (2016) found that drip irrigation at 1.5 PE up to maturity with 100 per cent RDF through water soluble fertiliser recorded the highest water use efficiency and water productivity of aerobic rice.…”
Section: Irrigation Scheduling (Iw/cpe) and Water Use Efficiency / Wa...mentioning
confidence: 94%